2018
DOI: 10.1177/0004563217748680
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of a routine versus an extensive laboratory analysis in the diagnosis of anaemia in general practice

Abstract: Background We investigated the percentage of patients diagnosed with the correct underlying cause of anaemia by general practitioners when using an extensive versus a routine laboratory work-up. Methods An online survey was distributed among 836 general practitioners. The survey consisted of six cases, selected from an existing cohort of anaemia patients ( n = 3325). In three cases, general practitioners were asked to select the laboratory tests for further diagnostic examination from a list of 14 parameters (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 14 publications
0
21
0
Order By: Relevance
“…This study has been retrospectively conducted in a cohort of patients formed by general practitioners (GPs) participating in a large project on anaemia evaluation improvement 8. Therefore, the patients’ involvement has been limited.…”
Section: Methodsmentioning
confidence: 99%
“…This study has been retrospectively conducted in a cohort of patients formed by general practitioners (GPs) participating in a large project on anaemia evaluation improvement 8. Therefore, the patients’ involvement has been limited.…”
Section: Methodsmentioning
confidence: 99%
“…In one study, the use of a limited laboratory analysis was compared to a more extensive laboratory analysis. They found that an extensive laboratory analysis leads more often to establishment of the anemia etiology [7]. Moreover, extensive laboratory analysis would prevent a delay in the initiation of treatment for the underlying disease and has shown to be cost-effective [8].…”
Section: Introductionmentioning
confidence: 99%
“…In this section, an explanation of the questionnaire and the database used in this questionnaire will be provided. A more extensive description was published previously [31].…”
Section: Methodsmentioning
confidence: 99%